Nephroprotective effect of soy (Glycine Max (L.) Merr.) flour against diazinon-induced renal toxicity in rats - Wisudanti, Desie Dwi; Normasari, Rena; Herdiyana, Firman (Faculty of Medicine, Universitas Trisakti, 2020)
BackgroundDiazinon is a widely used pesticide to eradicate agricultural pests globally with the potential to cause harmful effects on humans by generating free radicals and depleting endogenous antioxidants. Soy flour possesses high antioxidant effect. This study evaluated the nephroprotective effect of soy flour on diazinon-induced nephrotoxicity in rats. MethodsAn experimental laboratory study was carried out involving 30 male Wistar rats were randomly divided into five groups of 6 rats. The normal control (Kn) and the negative control (K-) groups received normal saline, the treatment groups (K1, K2, K3) received 10%, 15%, and 20% soy flour in distilled water, respectively, on day 1 to day 28. Subsequently, for five days, all groups received diazinon 40 mg/kg, except for the normal control group. Blood urea nitrogen (BUN) and creatinine levels were measured at the end of the study. The Kruskal Wallis test with the post hoc Mann Whitney U test were used to analyze the data. ResultsBlood urea nitrogen and creatinine levels were lower in all treatment groups (K1, K2, K3) compared to the negative control group (K-), while the K3 level was the lowest (24.28 ± 1.56 mg/dL and 0.93 ± 0.14 mg/dL). There was a significant decrease in BUN and creatinine levels in the experimental rats of the 15% and 20% soy flour groups (K2, K3) compared to the negative control group (K-).ConclusionAdministration of soy flour (Glycine max (L.) Merr.) had a nephroprotective effect in preventing increases in BUN and creatinine levels of diazinon-induced nephrotoxic male Wistar rats.